1995
DOI: 10.1007/bf00417860
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic modulation of smooth muscle cells during the formation of neointimal thickenings in the rat carotid artery after balloon injury: an electron-microscopic and stereological study

Abstract: The formation of neointimal thickenings in the rat carotid artery after balloon injury was studied by a combination of electron-microscopic and stereological methods. All smooth muscle cells in the normal media had a contractile phenotype, the cytoplasm being dominated by myofilaments. Seven days after endothelial denudation, the smooth muscle cells in the innermost part of the media had assumed a synthetic phenotype by loss of myofilaments and formation of a large endoplasmic reticulum and Golgi complex. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 34 publications
1
71
0
Order By: Relevance
“…1 proliferation is a key component of the response to vascular injury in atherosclerosis and restenosis in humans and following experimental angioplasty in animals (1)(2)(3). Several recent studies have focused interest on regulation of the cell cycle as a means of modulating this pathologic SMC growth (4 -6).…”
Section: Smooth Muscle Cell (Smc)mentioning
confidence: 99%
“…1 proliferation is a key component of the response to vascular injury in atherosclerosis and restenosis in humans and following experimental angioplasty in animals (1)(2)(3). Several recent studies have focused interest on regulation of the cell cycle as a means of modulating this pathologic SMC growth (4 -6).…”
Section: Smooth Muscle Cell (Smc)mentioning
confidence: 99%
“…We recently found that generation of Ang II in VSMC from SHR is associated with a change from the contractile to the synthetic phenotype, and that the change to the synthetic phenotype in SHR-derived VSMC also increases the expression of the growth factors of TGF-β1, PDGF A-chain, and bFGF through increased Ang II (33). VSMC proliferation and change to the synthetic phenotype contributes to the pathogenesis of atherosclerosis (34), neointimal formation after angioplasty (35) and hypertensive vascular diseases (36) in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Adult VSMCs are not terminally differentiated and may undergo major phenotypic changes in response to environmental stimuli (Fazekas et al 2007). Indeed, VSMCs may exhibit contractile or secretory phenotypes and have been observed to dedifferentiate following vascular injury (Campbell et al 1988;Thyberg et al 1995Thyberg et al , 1997. If one considers the contractile phenotype, the cells are spindle shaped and of the order of 80-200 mm long and 5 mm wide, whereas secretory VSMCs are smaller (approx.…”
Section: Development Of Ssms For Isrmentioning
confidence: 99%